3D chromosomal architecture in germinal center B cells and its alterations in lymphomagenesis. (June 2022) - Papin, Antonin; Cesarman, Ethel; Melnick, Ari
Abstract : In eukaryotic cells, the genome is three dimensionally (3D) organized with DNA interaction dynamics and topology changes that regulate gene expression and drive cell fate. Upon antigen stimulation, naive B cells are activated and form germinal centers (GC) for the generation of memory B cells and plasma cells. Thereby, terminal B-cell differentiation and associated humoral immune response require massive but rigorous 3D DNA reorganization. Here, we review the dynamics of genome reorganization during GC formation and the impact of its alterations on lymphomagenesis from the nucleosome structure to the higher order chromosome organization. We particularly discuss the identified architects of 3D DNA in GC B cells and the role of their mutations in B-cell lymphomas.